Early laser intervention to reduce scar formation in wound healing by primary intention: A systematic review. Issue 3 (March 2020) - Behrouz-Pirnia, Armin; Liu, Haibo; Peternel, Sandra; Dervishi, Gezim; Labeit, Alexander; Peinemann, Frank
Summary: Background: Hypertrophic scars frequently follow primary closure of surgical wounds. Laser application at or shortly after suture may be associated with a reduction in scar formation, although the respective study results vary. Aim: The objective was to evaluate the efficacy of early laser applied within the first six months after surgery to reduce scar formation compared to no treatment. Methods: We searched the databases MEDLINE and CENTRAL on 14 January 2019 and included randomized controlled trials (RCTs). Primary outcome was the Vancouver Scar Scale (VSS). Measure of treatment effect was the mean difference from baseline. Results: Seventeen relevant RCTs randomized 430 scars (413 assessed) and compared laser versus no treatment. Fourteen studies applied a split-scar and three applied a simple parallel design. Three studies with a split-scar design favored the laser group on VSS, and one study had indifferent findings. Considerable heterogeneity I 2  = 86% did not justify a meta-analysis. The remaining 13 studies did not report appropriate data. Conclusion: On the basis of the currently available evidence, we are uncertain whether early laser can reduce scar formation, and more high-quality research is needed for a definitive conclusion.